Alignment To CEFR And IELTS: The CELPAD IIUM Initiative - Abu Kassim, Noor Lide (2018)
The English Language Proficiency Test (EPT) has been in place at the International Islamic University Malaysia (IIUM) since the inception of the University in 1983. It has a longer history than the Malaysian University English Test (MUET), a national standardized English language proficiency test, which was first introduced in 1999 by the Malaysian Examinations Council. The EPT, which was first developed as a single test to determine the English language proficiency of incoming students, went through a number of revisions to complement the changes made to the curriculum of the English language support courses at the IIUM. After its last major revision, 25 years ago, the EPT is now going through a major transformation; the alignment to the Common European Framework (CEFR) and the IELTS. This paper describes how the construct alignment of EPT Reading Subtest to the CEFR Levels and IELTS was implemented and also its validation which was based on a pilot test involving 754 test takers and 40 reading test items covering nine reading subskills. Rasch analysis of the pilot data indicated that the targeting of the items generally support the construct alignment. However, the presence of off-target items suggests possible interaction effects between item format and test takers’ characteristics. Item developers’ intuitive impression that the first reading passage, targeted at B1, would be more challenging than the second passage, which was targeted at B2, was also confirmed. Overall, the results look promising and efforts are being made for better alignment to the CEFR and the IELTS.